A ANALYSIS OF STUDENTS' ANXIETY IN COMMUNICATION USING ENGLISH BY 4TH SEMESTER STUDENT OF HKBP NOMMENSEN UNIVERSITY OF MEDAN - Rina Octavia Simarmata; Yohana Sitompul; Yesica Hageltira Sitorus; Easter Apriani; Natasya Vany (Journal of Language Education (JoLE), 2025)
Abstract One of the main goals in learning English as an academic subject in Indonesia is to equip students with the ability to communicate effectively, both verbally and in writing. However, many students experience anxiety when asked to speak in English. These psychological barriers significantly inhibit their confidence and willingness to engage in verbal communication. This study explores the various forms and levels of anxiety experienced by students of the class of 2024 of the English Education Study Program at HKBP Nommensen University Medan. Using a qualitative method through a closed questionnaire and supported by class observation, this study identified emotional and behavioral indicators that are signs of language anxiety. The results show that most college students show moderate to high levels of anxiety, which often manifest in the form of fear, embarrassment, and hesitation when speaking in English. These findings confirm the importance of attention to affective factors in the language learning process to improve students' speaking skills and overall academic performance. Keywords: language anxiety, speaking skills, English education, psychological barriers, affective factors